Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5562/cca3570
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Electronic Influence of Guanidine Substitution on Diels-Alder Reactions of Heterocyclic Dienes

Abstract: Quantum-chemical calculations of cycloaddition properties of cyclic heterodienes substituted with guanidine functionality were carried out. Molecular and electronic structures of series of dienes (pyrrole, furan, thiophene, isoindole and 1,3-butadiene) were calculated and reactivity order established on the basis of FMO theory. Transition state calculations of model [4+2] cycloaddition reaction with acetylene indicate that guanidine substitution influences reaction barriers in moderate extent (up to ~4 kcal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The B3LYP/6-311+G(2d,p) method [18,19] was used to study the mechanism of azide addition to guanidine. Structures of reactants, transition states, and products were optimized without any symmetry constraints in the gas phase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The B3LYP/6-311+G(2d,p) method [18,19] was used to study the mechanism of azide addition to guanidine. Structures of reactants, transition states, and products were optimized without any symmetry constraints in the gas phase.…”
Section: Methodsmentioning
confidence: 99%
“…Different synthetic strategies are employed for the synthesis of tetrazoles [16]; however, the direct addition of azide to guanidine was not utilized. Realizing that this type of reaction has not been not theoretically studied to date, and in continuation of our interest in cycloaddition reactions [17,18] and study of the effects of the substitution of dienes with guanidines [19], we conducted this computational study to address several scientific questions: What is the reactivity of guanidine in 1,3-dipolar cycloadditions, and what is the regioselectivity of this reaction? This study aims to establish the cycloaddition (dipolarophilic) properties of imine bond in guanidine and the regioselectivity of the formation of tetrazoles.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this work is to prepare isoindole-2-carboxamidine 2, the first representative of an isoindole guanidine cycloaddition delivery reagent, and assess its cycloaddition properties experimentally and computationally. Our preliminary DFT computational study revealed that this approach is feasible and both pyrrole and isoindole dienes are predicted to have sufficient reactivity [14].…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, diamines have often been used in synthesis of novel basic organocatalysts [8][9][10] or fluorophores [11]. Triggered by these results, we became interested in using guanidine substituted dienes in cycloaddition reactions [12].…”
Section: Introductionmentioning
confidence: 99%